Fused‐Ring Core Engineering for Small Molecule Acceptors Enable High‐Performance Nonfullerene Polymer Solar Cells. Issue 11 (31st May 2019) - Ming, Ruijie; Wang, Jianxiao; Gao, Wei; Zhang, Miao; Gao, Jinhua; Ning, Weimin; Luo, Zhenghui; Liu, Xiaohui; Zhong, Cheng; Zhang, Fujun; Yang, Chuluo
Abstract: Small molecule acceptors (SMAs) for polymer solar cells (PSCs) have become a hot topic due to the resulting breakthrough of power conversion efficiency (PCE). To investigate the effect of extending central ladder‐type conjugated cores on the performance of PSCs, hexacyclic‐, heptacyclic‐, and octacyclic‐fused‐ring‐based SMAs (T6Me, T7Me, and T8Me) are designed and synthesized, structured with the same 2‐(1‐methyl‐6‐oxo‐5, 6‐dihydro‐4 H ‐cyclopenta[ c ]thiophen‐4‐ylidene)malononitrile (CPTCN‐M) termini. The extension of backbone conjugation leads to the red shift of the absorption spectra, and elevates both the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) energy levels. Pairing with polymer donor PM6, T6Me‐based PSC displays a higher PCE of 12.09% than T7Me‐ (PCE of 8.96%) and T8Me‐based PSCs (PCE of 6.09%). This trend is ascribed to the lower bimolecular recombination, more favorable morphology features as well as more balanced hole and electron mobilities in the PM6:T6Me blend. Moreover, the low optical gap of T6Me and relatively high open‐circuit voltage ( V OC ) for the PM6:T6Me blend film results in low energy loss ( E loss ) of 0.51 eV. Abstract : Three small molecular acceptors, namely T6Me, T7Me, and T8Me, are designed and synthesized by fused‐ring core engineering to investigate the effect of extending central ladder‐type conjugated core on the performance of polymer solar cells (PSCs). T6Me‐based PSCs present a good power conversion efficiency of 12.09%.